2021
DOI: 10.1038/s41467-021-24776-4
|View full text |Cite
|
Sign up to set email alerts
|

Human sensorimotor organoids derived from healthy and amyotrophic lateral sclerosis stem cells form neuromuscular junctions

Abstract: Human induced pluripotent stem cells (iPSC) hold promise for modeling diseases in individual human genetic backgrounds and thus for developing precision medicine. Here, we generate sensorimotor organoids containing physiologically functional neuromuscular junctions (NMJs) and apply the model to different subgroups of amyotrophic lateral sclerosis (ALS). Using a range of molecular, genomic, and physiological techniques, we identify and characterize motor neurons and skeletal muscle, along with sensory neurons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 110 publications
1
79
0
1
Order By: Relevance
“…Even if iPS-derived macrophages/microglia were the first generated immune cells, there is no report yet about iPSC modeling of ALS or FTD macrophage/microglia co-cultures with neurons. In their recent study, Pereira et al (2021) describes the generation of human sensorimotor organoids with iPSC from ALS patients. They showed that these organoids contain microglia-like cells, but their study was not focused on the phenotypes of these cells, but rather on defects at the level of NMJs ( Pereira et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if iPS-derived macrophages/microglia were the first generated immune cells, there is no report yet about iPSC modeling of ALS or FTD macrophage/microglia co-cultures with neurons. In their recent study, Pereira et al (2021) describes the generation of human sensorimotor organoids with iPSC from ALS patients. They showed that these organoids contain microglia-like cells, but their study was not focused on the phenotypes of these cells, but rather on defects at the level of NMJs ( Pereira et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their recent study, Pereira et al (2021) describes the generation of human sensorimotor organoids with iPSC from ALS patients. They showed that these organoids contain microglia-like cells, but their study was not focused on the phenotypes of these cells, but rather on defects at the level of NMJs ( Pereira et al, 2021 ). Another study describes the generation of cerebral organoids from iPSC of 3 FTD patients mutated in the tau gene ( Bowles et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, organoid culture systems allow for the differentiation of multiple cell types to form a miniature version and experimentally approachable model of the tissue of interest ( Vieira de Sa et al, 2021 ). Recently, iPSC-derived human sensorimotor organoids, which contain motor and sensory neurons, skeletal muscle, astrocytes, microglia, and vasculature, have been used to assess how familial ALS mutations affect NMJ and muscle function in vitro ( Pereira et al, 2021 ).…”
Section: Enhancing Cell Maturity and Exploring Cell Biological Mechanismsmentioning
confidence: 99%
“…Moreover, fusion of brain organoids is currently used to model interactions between different brain regions [71]. The development of additional tissues, like bilateral optical vesicles [72], or even the fusion with muscle cells for the development of motoneurons and of neuromuscular junctions, [73], [74] have been performed and these studies exemplified the advantages ahead using organoids to study human brain diseases. Thus, these approaches will prove useful in the future to investigate in further detail, how FOXG1 influences later neural development, its potential influence on tissue interaction, on entire organ function, and even multi-organ interplay.…”
Section: Future Of Foxg1 Syndrome Modelling Therapeutic Prospects and Limitationsmentioning
confidence: 99%